2018
DOI: 10.3892/mmr.2018.8545
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of aquaporin 1 decreased ADAMTS‑4 expression in human chondrocytes

Abstract: Inflammation serves an important role in the progression of osteoarthritis (OA), and IL-1β may act as a catabolic factor on cartilage, reducing the synthesis of primary cartilage components type II collagen and aggrecan. Aquaporin 1 (AQP1) is a 28-kDa water channel formed of six transmembrane domains on the cell membrane. AQP1 is highly expressed in the anus, gallbladder and liver, and is moderately expressed in the hippocampus, ependymal cells of the central nervous system and articular cartilage. It was hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…The reasons may be that the expression of ADAMTS-4 was inducible and sensitive to IL-1β stimulation, while the expression of ADAMTS-5 was constitutive and insensitive to the induction of IL-1β. These results were consistent with previous studies on the effect of IL-1β on the expression of ADAMTS-4/-5 associated with individual differences and enzyme activity in human OA chondrocytes [37,38]. This result suggested that both ADAMTS-4/-5 contributed to the degradation of cartilage aggrecan in IL-1β-treated human OA chondrocytes, while ADAMTS-4 seemed more sensitive to IL-1β in vitro.…”
Section: Discussionsupporting
confidence: 93%
“…The reasons may be that the expression of ADAMTS-4 was inducible and sensitive to IL-1β stimulation, while the expression of ADAMTS-5 was constitutive and insensitive to the induction of IL-1β. These results were consistent with previous studies on the effect of IL-1β on the expression of ADAMTS-4/-5 associated with individual differences and enzyme activity in human OA chondrocytes [37,38]. This result suggested that both ADAMTS-4/-5 contributed to the degradation of cartilage aggrecan in IL-1β-treated human OA chondrocytes, while ADAMTS-4 seemed more sensitive to IL-1β in vitro.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, MMP-13, MMP-3, MMP-2, and MMP-9 increased in the cell line model of osteoarthritis [26,28]. Furthermore, several studies have investigated the MMP-13 level in osteoarthritis patients, and consistent observation is obtained, whereby the MMP-13 level increased significantly in patients with osteoarthritis [30,48,59,[73][74][75][76][77][78]. MMP-13, as a collagenase, is responsible for the degradation of type II collagen [79], which is the main collagen type in articular cartilage [80].…”
Section: The Role Of Matrix Metalloproteinases (Mmps) In Osteoarthritismentioning
confidence: 67%
“…Hou et al showed that chemokine CX3CL1 induces MMP-3 production in a concentration-dependent and timedependent manner using synovial fibroblasts from patients with osteoarthritis (OASFs) [9]. Other than that, several studies showed increased MMP-3 in osteoarthritis [47,48,53,73,78,82,83]. The induction of MMP-3 has been related to miR-149 and miR-454 expression in osteoarthritis [51,84].…”
Section: The Role Of Matrix Metalloproteinases (Mmps) In Osteoarthritismentioning
confidence: 99%
“…The inflammatory markers, especially interleukins [ 27 ] (ILs) and matrix metalloproteinases [ 28 30 ] (MMPs) have been widely investigated. In previous studies, IL-1β has been shown to play a key role in the development and progression of OA [ 31 , 32 ]. The results of Özler K et al [ 33 ] showed that MMP-13 expression in the joint fluid of patients with severe KOA was significantly related to the WOMAC score.…”
Section: Discussionmentioning
confidence: 99%